Scaling-up phase selection. Issue 12 (December 2018) - Mohite, Aditya; Blancon, Jean-Christophe
A method to selectively grow pure metallic-phase monolayer transition metal dichalcogenides marks an important step towards industrially viable nano-(opto)electronic technologies based on two-dimensional materials and their hierarchical assemblies.